2020
DOI: 10.1029/2019ea000953
|View full text |Cite
|
Sign up to set email alerts
|

Robust Adaptive Spacecraft Array Derivative Analysis

Abstract: Multispacecraft missions such as Cluster, Themis, Swarm, and MMS contribute to the exploration of geospace with their capability to produce gradient and curl estimates from sets of spatially distributed in situ measurements. This paper combines all existing estimators of the reciprocal vector family for spatial derivatives and their errors. The resulting framework proves to be robust and adaptive in the sense that it works reliably for arrays with arbitrary numbers of spacecraft and possibly degenerate geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Note that in Vogt et al (2013) the symbol R is used for the position tensor. In this paper we adhere to the notations from Vogt et al (2020), where R designates the position matrix and the position tensor is indicated by R pos (see below).…”
Section: Dual-satellite Fac Estimation By Least Squaresmentioning
confidence: 99%
See 4 more Smart Citations
“…Note that in Vogt et al (2013) the symbol R is used for the position tensor. In this paper we adhere to the notations from Vogt et al (2020), where R designates the position matrix and the position tensor is indicated by R pos (see below).…”
Section: Dual-satellite Fac Estimation By Least Squaresmentioning
confidence: 99%
“…The dual-satellite SVD algorithm from SwarmFACE represents an adaptation of the more general RASADA (from Robust Adaptive Spacecraft Array Derivative Analysis) method and code developed in Vogt et al (2020). RASADA allows to estimate the spatial derivative of physical quantities and their corresponding errors from an array of arbitrary numbers of satellites/observation points.…”
Section: Dual-satellite Fac Estimation By Singular Value Decompositionmentioning
confidence: 99%
See 3 more Smart Citations